SILENT COMEDIANS. THE OLSZTYN PANTOMIME OF DEAF (1957–2009). IN SEARCH OF A NEW AESTHETIC OF EXPRESSION - SOKOŁOWSKI MAREK (Наука телевидения)
The purpose of this article is to recall the significance of the Olsztyn Deaf Pantomime in Polish theatre culture, and a special role in its creation of professor Bohdan Głuszczak, who was an actor, theatre director, and artistic visionary. Professor Głuszczak, despite many adversities, created a pantomime theatre, with deaf actors. In the following article, the historical aspect of Pantomime is briefly recalled in the first two parts of the article, followed by a short bio of its creator Bohdan Głuszczak and his vision of work with deaf artists. His work was based on the concept of art-therapy treatment, and education (including aesthetic) participation in theatre classes (1). Next, Pantomime’s artistic heritage (from twenty-two performances by Głuszczak) is presented, with emphasis on the most popular performances that were ultimately exhibited in many countries around the world. The issue of the how the stage visions was reflected in eight films, created both on the basis of ready pantomimic performances, as well as inspired by the mimes from Olsztyn remains an important cognitive issue for the author of this article. The hypothesis of the author is that a film is so distinct from the pantomime theatre, that the audience who had not previously experienced the performances of the Olsztyn Deaf Pantomime could not fully feel the artistic power directly emanating from the performances. The power of performances was especially captivating for live audience, both in the aesthetic of the performances, their choreography, music, costumes, stage design, as well as the artistic skill and excellence of the actors. It is also noteworthy, that actors were amateurs, lacking a professional training. The study ends with an attempt to summarize this special and unique artistic phenomenon, which was certainly the Olsztyn Deaf Pantomime.